2020
DOI: 10.1002/acn3.51112
|View full text |Cite
|
Sign up to set email alerts
|

11C‐PK11195 PET–based molecular study of microglia activation in SOD1 amyotrophic lateral sclerosis

Abstract: Objective Neuroinflammation is considered a key driver for neurodegeneration in several neurological diseases, including amyotrophic lateral sclerosis (ALS). SOD1 mutations cause about 20% of familial ALS, and related pathology might generate microglial activation triggering neurodegeneration. 11C‐PK11195 is the prototypical and most validated PET radiotracer, targeting the 18‐kDa translocator protein which is overexpressed in activated microglia. In this study, we investigated microglia activation in asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 87 publications
2
21
0
Order By: Relevance
“…In human ALS 31,32 , and in pre-symptomatic carriers of SOD1 mutations 33 , widespread cerebral microglial activation was demonstrated by PET imaging in vivo. In post mortem ALS, elevated levels of microglial transcripts, increased microglial density, and activated microglial morphology have been found in addition to motor neuron degeneration 34,35 .…”
Section: Glia In Cns Physiology and Human Als Microgliamentioning
confidence: 99%
“…In human ALS 31,32 , and in pre-symptomatic carriers of SOD1 mutations 33 , widespread cerebral microglial activation was demonstrated by PET imaging in vivo. In post mortem ALS, elevated levels of microglial transcripts, increased microglial density, and activated microglial morphology have been found in addition to motor neuron degeneration 34,35 .…”
Section: Glia In Cns Physiology and Human Als Microgliamentioning
confidence: 99%
“…Some studies have explored the role of microglial activation in ALS [36,37], AD [38,39] and MS [40][41][42]. While these studies report significantly increased microglial activation, as inferred from increased TSPO binding, some studies have demonstrated no correlation between microglial activation and increased TSPO binding [40][41][42].…”
Section: Microglia Are Never-resting Sensors Of Pathologymentioning
confidence: 99%
“…More recently, specific increased expression of cannabinoid receptor type 2 (CB2r) and purinergic P2X7 (P2X7r) receptors have been reported in activated microglia cells in ALS rodent models and patients' post-mortem samples. CD68 immunostaining and TSPO-ligand binding were increased in CNS areas displaying positivity for CB2r and P2X7r, supporting the association of these markers with compromised CNS districts characterized by ongoing neuroinflammatory processes and microglia cell activation [103]. This has prompted the development of radioligands targeted to CB2r and P2X7r as sensitive PET tracers alternative/complementary to TSPO-ligands, with some promising candidate compounds already validated at pre-clinical level [104].…”
Section: Neuroinflammation As a Diagnostic/prognostic Markermentioning
confidence: 81%